Empowerment of Employees through Training and Seminar that Leads to Customer Satisfaction in Accounting Services: Vol.3, No.1A (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
As entrepreneurship arises, the need for accounting firms also arises. Clients expect their accountants to be up to date on how financial data and other accounting information may be entered, accessed, and debated in a concise amount of time as the internet and cloud technology continue to disrupt many industries, including accounting. Jadivic Administrative and Business Management Services Incorporated was formerly Jadivic Accounting Services. It is an accounting and consulting firm established in 2012 by Mrs. Dianne Loise Estanislao Agojo and Company, which is associated with Estanislao, Mamuri & Co., CPAs as Co-owners. The firm specializes in auditing, business consultation, tax planning, and accounting services. The descriptive method was scientifically employed with comparative techniques and correlational analysis. The researcher treated the surveyed data through frequency counts, means and percentage computations, and analysis of variance/t-test to compare two main area variables. The study has 50 total respondents, 36 (72%) clients and 14 (28%) employees of Jadivic Inc. The result assessing the program of the company in terms of designation of tasks agreed by most of the employees with a 3.17 weighted mean and clients 3.06 weighted mean, while in terms of behaviour towards clients, the majority of the employees agree with a 3.33 weighted mean and the clients are strongly agree with a total weighted mean of 3.36. Lastly, regarding adaptation to changes, employees (3.21) and clients (3.51) agreed with its total weighted mean. The researcher recommends that the future hired employees must be degree holders. Researchers also recommend Jadivic Inc., such as handling clients' training about being a reliable accountant. This will help improve employees' skills. Also, always setting calendars ahead of time is one of the researcher's recommendations, as is continuing to provide free webinars and consultations to every client.
Keywords: customer satisfaction; training and seminar